PSYCHOLOGICAL MENTALITY IN THE XXI CENTURY: IDEOLOGICAL REVIVALS AND THE IMPORTANCE OF HUMAN GOALS - Karimov Sayimnazar Karimovich; Jamilov Firdavs Otabek o’g’li; Rafiqjonov Damir Raxim o’g’li (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Abstract: This article is intended to explore the importance of psychological minimalism in the 21st century in connection with ideological reconstructions and human goals. The article emphasizes the importance of ideological permutations in the process of self-determination of people, setting goals and achieving them. It discusses the place occupied by ideological perestroika and their impact on the psychological mentality when people explore their human potential and strive for higher goals and meanings. The article, in particular, will consider the psychological process of self- knowledge, achievement of goals and current problematic situations in achieving internal stability by people, scientifically based conclusions and suggestions on this issue are given.